2013
DOI: 10.1177/0269215513476722
|View full text |Cite
|
Sign up to set email alerts
|

Effects of balance training on functional outcome after total knee replacement in patients with knee osteoarthritis: a randomized controlled trial

Abstract: Additional balance training exerted a significant beneficial effect on the function recovery and mobility outcome in patients with knee osteoarthritis after total knee replacement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
66
0
12

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 63 publications
(86 citation statements)
references
References 37 publications
(61 reference statements)
8
66
0
12
Order By: Relevance
“…Because being overweight or obese is a risk factor for poor postural stability (56)(57)(58), and because changes in body weight influence balance control (59,60), it is reasonable to expect that overweight and obese patients perform more poorly in the FRT and SLS test compared with patients with a normal BMI, because such tasks are highly dependent on postural stability and balance control. Previous studies have shown that the performance of postural stabilitydependent mobility tasks improves after balance-based post-TKR rehabilitation (24,38), which is consistent with the significant improvements in the FRT and SLS test results for all of the BMI groups at the 2-month and 6-month post-TKR followup assessments in the current study.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Because being overweight or obese is a risk factor for poor postural stability (56)(57)(58), and because changes in body weight influence balance control (59,60), it is reasonable to expect that overweight and obese patients perform more poorly in the FRT and SLS test compared with patients with a normal BMI, because such tasks are highly dependent on postural stability and balance control. Previous studies have shown that the performance of postural stabilitydependent mobility tasks improves after balance-based post-TKR rehabilitation (24,38), which is consistent with the significant improvements in the FRT and SLS test results for all of the BMI groups at the 2-month and 6-month post-TKR followup assessments in the current study.…”
Section: Discussionsupporting
confidence: 91%
“…Performance-based tasks, such as the FRT, SLS test, TUG test, CRT, TMWT, and SCT, are used as measures to evaluate balance and mobility outcomes following post-TKR rehabilitation (18,20,21,24,38,(49)(50)(51). However, the impact of a high BMI on such clinical outcomes has not been clarified completely.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations